Relations between maternal power‐assertive parenting and adjustment in Chinese children: A longitudinal study. (29th January 2019) - Xu, Xinpei; Zhao, Siman; Yiu, Wai Ying Vivien; Li, Dan; Liu, Junsheng; Liu, Shihong; Chen, Xinyin
Abstract : This 1‐year longitudinal study examined relations between maternal power‐assertive parenting and children's social, academic and psychological adjustment in China. Participants were 316 elementary school children ( mean age = 11 years, 153 boys). Maternal power‐assertive parenting was assessed using children's self‐reports. Data on children's social and school adjustment were obtained from peer evaluations and teacher ratings. In addition, children completed measures of loneliness and depression. Cross‐lagged analyses indicated that whereas maternal power‐assertive parenting was only related to later academic adjustment, children's adjustment in socioemotional and academic domains contributed to the prediction of later maternal power‐assertive parenting. The results were discussed in the Chinese context.